2023
DOI: 10.1038/s41467-023-36092-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient stabilization of cyanonaphthalene by fast radiative cooling and implications for the resilience of small PAHs in interstellar clouds

Abstract: After decades of searching, astronomers have recently identified specific Polycyclic Aromatic Hydrocarbons (PAHs) in space. Remarkably, the observed abundance of cyanonaphthalene (CNN, C10H7CN) in the Taurus Molecular Cloud (TMC-1) is six orders of magnitude higher than expected from astrophysical modeling. Here, we report unimolecular dissociation and radiative cooling rate coefficients of the 1-CNN isomer in its cationic form. These results are based on measurements of the time-dependent neutral product emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 51 publications
(108 reference statements)
2
33
0
Order By: Relevance
“…29,30 The methods used here have largely been described previously. 6,16 Briefly, 1-CNN (Sigma-Aldrich, >96%) was sublimed from powder in a resistively heated oven coupled to an electron cyclotron resonance (ECR) ion source (Pantechnik Monogan) using helium as a support gas. Cations extracted from the source were accelerated to 34 keV kinetic energy.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…29,30 The methods used here have largely been described previously. 6,16 Briefly, 1-CNN (Sigma-Aldrich, >96%) was sublimed from powder in a resistively heated oven coupled to an electron cyclotron resonance (ECR) ion source (Pantechnik Monogan) using helium as a support gas. Cations extracted from the source were accelerated to 34 keV kinetic energy.…”
Section: Methodsmentioning
confidence: 99%
“…We adopt the parameters from our earlier study, 6 which found a rather small reverse barrier height ∆E = 7.6(4) meV and a transition state frequency hω = 350(20) cm −1 from simultaneous fits to the KER distributions for spontaneously decaying 1-CNN up to 20 ms after ionization. That study also found the dissociation rate coefficient to follow a modified Arrhenius expression:…”
Section: Kinetic Energy Release Distributionsmentioning
confidence: 99%
See 3 more Smart Citations